Generalized Amply Cofinitely Supplemented Modules - Elewi, Alaa (Iraqi Journal of Science, 2023)
Let R be an associative ring with identity. An R-module M is called generalizedamply cofinitely supplemented module if every cofinite submodule of M has anample generalized supplement in M. In this paper we proved some new results aboutthis conc- ept.